2002
DOI: 10.1094/mpmi.2002.15.12.1195
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas viridiflava and P. syringae—Natural Pathogens of Arabidopsis thaliana

Abstract: We report the isolation and identification of two natural pathogens of Arabidopsis thaliana, Pseudomonas viridiflava and Pseudomonas syringae, in the midwestern United States. P. viridiflava was found in six of seven surveyed Arabidopsis thaliana populations. We confirmed the presence in the isolates of the critical pathogenicity genes hrpS and hrpL. The pathogenicity of these isolates was verified by estimating in planta bacterial growth rates and by testing for disease symptoms and hypersensitive responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
105
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 65 publications
3
105
0
Order By: Relevance
“…We were surprised to find a 390 single dominant Pseudomonas lineage in the study area, given that wild A. thaliana populations can be colonized 391 by a diversity of Pseudomonas pathogenic species (Jakob et al, 2002;Kniskern et al, 2011). We note, though, 392 that while the OTU5 strains share many genetic features, they are not functionally synonymous--instead they 393 are differentiated both at the level of gene content and the level of virulence.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…We were surprised to find a 390 single dominant Pseudomonas lineage in the study area, given that wild A. thaliana populations can be colonized 391 by a diversity of Pseudomonas pathogenic species (Jakob et al, 2002;Kniskern et al, 2011). We note, though, 392 that while the OTU5 strains share many genetic features, they are not functionally synonymous--instead they 393 are differentiated both at the level of gene content and the level of virulence.…”
mentioning
confidence: 90%
“…Arabidopsis thaliana is a globally distributed wild plant 64 capable of colonizing poor substrates as well as fertilised soils (Weigel, 2012). Arabidopsis thaliana populations 65 across the globe are hosts to Pseudomonas, and several of the most abundant Pseudomonas strains are 66 pathogenic on A. thaliana, even though they are likely not specialized on this species as a host (Barrett et al, 67 2011;Bodenhausen et al, 2014; Cai et al, 2011;Jakob et al, 2002Jakob et al, , 2007Kniskern et al, 2011). 68…”
mentioning
confidence: 99%
“…In a previous study, we identified two paralogous PAIs in P. viridiflava , a prevalent natural pathogen of A. thaliana ( Jakob et al 2002). Although these PAIs (T-and S-PAI, respectively) share 25 gene homologs, they are structurally distinct.…”
mentioning
confidence: 96%
“…We investigate the generality of these changes in development by examining the effects of three distantly related pathogens: P. syringae and Xanthomonas campestris, which are biotrophic bacterial pathogens, and Peronospora parasitica, which is a biotrophic oomycete. All of these pathogens occur in natural Arabidopsis populations (Tsuji and Somerville, 1992;Holub et al, 1994;Jakob et al, 2002). We also address how the amount of pathogen in a plant affects development and whether R gene resistance affects developmental responses to pathogen infection.…”
mentioning
confidence: 99%